Effectiveness of Cell Management Education for Patients with Diabetes Mellitus: A Systematic Review - Arian Febrila Dewanti, Neni; Susanti, Indah; Fikar Lanjari, Zul; Feibirini, Fitri (Java Nursing Journal, 2023)
Background: Diabetes mellitus is a chronic disease that ranks as the fourth leading cause of death in developing countries. The main pillars in the management of type 2 Diabetes Melitus (T2DM) are education, nutritional therapy, physical training, and pharmacological interventions. The provision of education that has had a positive impact on DM patients is the Diabetes Self-Management Education (DSME). Method: The purpose of this study was to evaluate the effectiveness of the application and web-based Diabetes Self-Management Education (DSME) method in patients with type 2 DM. This study used a systematic literature review design. Articles were collected through PubMed and Google Scholar databases using the keywords DSME Web Application, DSME Smartphone. The criteria for articles used were those published from 2014-2020. Results: the literature review show that the application-based DSME method is more effective in improving self-management of type 2 DM sufferers. Search for articles related to 9 sources that fall within the criteria. Conclusion: is that the application-based DSME method is more effective because it does not require a lot of money and a long time compared to doing direct control to health facilities, the application can also always be accessed whenever we want so that it can help improve self-management in people with Diabetes Mellitus